On Optimum Multi-installment Divisible Load Processing in Heterogeneous Distributed Systems - Drozdowski, Maciej; Lawenda, Marcin (Euro-Par 2005 Parallel Processing, 2005)
In this paper we study multi-installment divisible load processing in heterogeneous distributed systems. Divisible loads are computations which can be divided into parts of arbitrary sizes, and these parts can be processed independently in parallel. In order to reduce the waiting time during the parallel computation initialization phase, load is sent to the processors in multiple small installments. In a heterogeneous system the sizes of the installments should be adjusted to the communication, and computation capabilities of the processors. We propose two algorithms that gear the load chunk sizes to different communication and computation speeds. The first one is an optimization branch and bound algorithm. The second algorithm is based on genetic search. The running times of both methods and the quality of the genetic algorithm solutions are compared. Then, we use these algorithms to analyze features of the scheduling problem solutions.